SMRT Sequencing of the Full-Length Transcriptome of the Coelomactra antiquata - Deng, Aiping; Li, Jinpeng; Yao, Zebin; Afriyie, Gyamfua; Chen, Ziyang; Guo, Yusong; Luo, Jie; Wang, Zhongduo (Frontiers in Genetics, 2021)
Coelomactra antiquata is an important aquatic economic shellfish with high medicinal value. However, because C. antiquata has no reference genome, a lot of molecular biology research cannot be carried out, so the analysis of its transcripts is an important step to study the regulatory genes of various substances in C. antiquata. In the present study, we conducted the first full-length transcriptome analysis of C. antiquata by using PacBio single-molecule real-time (SMRT) sequencing technology. The results identified a total 39,209 unigenes with an average length of 2,732bp, 23,338 CDSs, 251 AS events, 9881 lncRNAs, 20,106 SSRs and 2,316 TFs. Subsequently, 59.22% (23220) of the unigenes were successfully annotated, of which 23,164, 18,711, 15,840, 13,534 and 13,474 unigenes could be annotated using NR, Swiss-prot, KOG, GO and KEGG databases respectively. This study lays the foundation for the follow-up research of molecular biology, and provides a reference for studying the more medicinal value of C. antiquata.